Symbolic Pathways to Sustainability: An Approach to Natural Resource Stewardship - Upadhyay, Prakash; Paudel, Shanaar Nath (The Himalayan Geographers, 2024)
This article examines how symbolism, which represented a paradigm shift away from utilitarian and functionalist frameworks, emerged and affected sociology and anthropology in the 1960s and 1970s. Symbolism, pioneered by researchers like Clifford Geertz, Mary Douglas, and Victor Turner, stresses an interpretative approach to understanding culture. According to this paradigm, culture is viewed as a dynamic ‘web of significance,’ in which language, rituals, and daily activities all function as symbols that are essential for creating meaning in particular social circumstances. The article also explores how, especially when viewed through the prism of indigenous knowledge systems, this symbolic approach broadens our comprehension of the connection between culture, society, and the management of natural resources. Drawing on secondary sources, it examines how traditional ecological knowledge, embedded in symbolic practices, complements and enhances modern conservation efforts. Case studies, such as rituals associated with forests and water in Nepal, highlight how cultural symbols bridge the material and immaterial dimensions of culture. These symbols foster sustainable resource use, demonstrating the critical role they play in shaping human-environment interactions. The findings stress the importance of integrating sociocultural symbols and local worldviews into conservation strategies, as they are essential in promoting ecological sustainability.